Parvovirus Infection and Congenital Leukemia: Is It a Causal or Casual? - RA, Dasrilsyah; S, Ahmad; GC, Tan; PS, Lim (IIUM Medical Journal Malaysia, 2017)
Congenital leukemia is an extremely rare disease but frequently fatal. We report a case of intrauterine death (IUD) secondary to congenital erythroid leukaemia associated with maternal Parvovirus B19 infection. Further research is needed to ascertain the association between maternal Parvovirus B19 infection and congenital leukemia.